Hybrid magnetic GO·CNT·Fe3O4 nanomaterial for escitalopram removal: Synthesis, characterization, adsorption mechanisms, and biosafety assessment - Leonardo Vidal Zancanaro; Taíse Regina Schuster Montagner; Najla AlMasoud; Taghrid S. Alomar; Franciane Batista Nunes; Theodoro da Rosa Salles; Alana Torres Viero; Claudir Gabriel Kaufmmann Junior; Arthur Harres de Oliveira; Bernhard Westermann; Alencar Kolinski Machado; Sérgio Roberto Mortari; et al. (Journal of Environmental Chemical Engineering, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Quick guide to secondary metabolites from Apiospora and Arthrinium - Marie L. Overgaard; Trine Aalborg; Emil J. Zeuner; Klaus R. Westphal; Frederik A. Lau; Vibeke S. Nielsen; Kasper B. Carstensen; Emil A. Hundebøll; Tia A. Westermann; Gustav G. Rathsach; Jens L. Sørensen; Jens C. Frisvad; et al. (Fungal Biology Reviews, 2023)

Esperanto for histones: CENP-A, not CenH3, is the centromeric histone H3 variant - W. C. Earnshaw; R. C. Allshire; B. E. Black; K. Bloom; B. R. Brinkley; W. Brown; I. M. Cheeseman; K. H. A. Choo; G. P. Copenhaver; J. G. DeLuca; A. Desai; S. Diekmann; et al. (Chromosome Research, 2013)

Influence of (S)-ketamine on human motor cortex excitability - Oliver Höffken; Ida S. Haussleiter; Andrea Westermann; Jörn Lötsch; Christoph Maier; Martin Tegenthoff; Peter Schwenkreis (Experimental Brain Research, 2013)

Exploring the genome sequence of Bifidobacterium bifidum S17 for potential players in host-microbe interactions - Christina Westermann; Daria S. Zhurina; Annika Baur; Wei Shang; Jing Yuan; Christian U. Riedel (Symbiosis, 2012)

Metallophilic macrophages are fully developed in the thymus of autoimmune regulator (Aire)-deficient mice - Novica M. Milićević; Živana Milićević; Miloš D. Miljković; Milica Labudović-Borović; Martti Laan; Pärt Peterson; Kai Kisand; Hamish S. Scott; Ning Qu; Jürgen Westermann (Histochemistry and Cell Biology, 2009)

Effect of repeated treatment with high doses of selegiline on behaviour, striatal dopaminergic transmission and tyrosine hydroxylase mRNA levels - Themann C.; D. Alvarez Fischer; Groß S.; Westermann R.; Weihe E.; Kuschinsky K.; Schäfer M.; Ferger B. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Sensitization to the behavioural effects of cocaine: alterations in tyrosine hydroxylase or endogenous opioid mRNAs are not necessarily involved - D. Alvarez Fischer; M.K.H. Schäfer; B. Ferger; S. Groß; R. Westermann; E. Weihe; K. Kuschinsky (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

A genetic linkage map of rye (Secale cereale L.) - V. Korzun; S. Malyshev; N. Kartel; T. Westermann; W. E. Weber; A. Börner (Theoretical and Applied Genetics, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Nutrient concentration relationships between the fourth petiole and upper-stem of potato plants - D. T. Westermann; S. M. Bosma; M. A. Kay (American Journal of Potato Research, 1994)